posted by Yadira on .
Prove the identit: cosxcotx+sinx=cscx
1) rewrite cosx (cosx/sinx) + sinx = csc x
2) cosx^2/sinx + sinx = csc x
3) multiply sinx by (sinx/sinx) to get same denominator
this gives you cosx^2/sinx + sinx^2/sinx = cscx
4) combine your fractions
(cosx^2 + sinx^2)/sinx = cscx
5) rewrite numerator
1/sinx= csc x
and there you go it is proven (you have to know your trig identity to do this so look them up if you don't know them)
Thank You! :D
no problem lol this one almost had me stump for alittle
Ohh it was hard me :/ .Do you think you can answer my other questions?